PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN THE INFLUENCES OF BRAND EQUITY TO BUYING DECISION - Menur Ajeng Retnowati (MNJ 16 UMY 158, 2016)
This study aims to analyze the influences of brand equity to buying decision. The sampling method used ini this study is non – probability sampling with purposive sampling. In this study, the respondents were 96 consumers of face and hair care service on Larissa Aesthetic Center at Yogyakarta. This study using multiple regression linier which run on spss 15.0 as analysis tool. The multiple regression results as equation showed Y = 0,216 X1+ 0,160X2 + 0,174X3+0,469X4. The biggest effect on buying decisions is brand loyalty variable (X4) with coefficient 0,469. The second one followed by brand awareness with coefficient0,174. For the independent variable which has the suallest affect is perceived quality (x2) with coefficient 0,160 hypothesis testing by F test showed four independent variables simultaneously have significant affect to buying decision. Next, by t test showed each independent variables have positive significant effect to buying decision. Adjusted R square number is 63,3% which is buying decision can be explained by brand awareness, perceived quality, brand association, brand loyalty mean while 32% can be explained by others varian variables which are out of this research, e.g. brand image Keywords : brand awareness, perceived quality, brand association, brand loyalty, buying decision.